2011
DOI: 10.21273/jashs.136.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salt-induced Changes in Leaf and Root Proteomes of the Wild Tomato, Solanum chilense

Abstract: This article reports salt-induced changes in leaf and root proteomes after wild tomato (Solanum chilense) plants were treated with 200 mm NaCl. In leaf tissues, a total of 176 protein spots showed significant changes (P < 0.05), of which 104 spots were induced and 72 spots suppressed. Salt-induced proteins are associated with the following pathways: photosynthesis, carbohydrate metabolism, glyoxylate shunt, glycine cleavage sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 62 publications
3
22
0
4
Order By: Relevance
“…The inhibition of growth observed in many plants under salinity conditions is usually associated with several physiological disturbances, including ion toxicity, osmotic stress and generation of reactive oxygen species (ROS; Parida and Das, 2005). Zhou et al (2011) recently conducted a thorough proteomic analysis in S. chilense and demonstrated that salt-induced proteins are mainly associated with selective ion transport, carbohydrate metabolism and antioxidant activities. It was also recently demonstrated that S. chilense displays a fascinating ability to cope with salt-induced oxidative stress at the seedling stage (Martínez et al, submitted).…”
Section: Solanum Lycopersicum Solanum Chilensementioning
confidence: 99%
“…The inhibition of growth observed in many plants under salinity conditions is usually associated with several physiological disturbances, including ion toxicity, osmotic stress and generation of reactive oxygen species (ROS; Parida and Das, 2005). Zhou et al (2011) recently conducted a thorough proteomic analysis in S. chilense and demonstrated that salt-induced proteins are mainly associated with selective ion transport, carbohydrate metabolism and antioxidant activities. It was also recently demonstrated that S. chilense displays a fascinating ability to cope with salt-induced oxidative stress at the seedling stage (Martínez et al, submitted).…”
Section: Solanum Lycopersicum Solanum Chilensementioning
confidence: 99%
“…Therefore, comparative proteomic approaches are powerful and promising tools for investigating plant stress responses. Several studies focused on proteomic changes in different plant organs, including roots and leaves, in response to salt stress in soybean ( Glycine max ), [ 14 ] and in wild tomato ( Solanum chilense ) [ 15 ]. Proteomic changes in leaves of wild and modern wheat under drought stress were studied to determine the differentially expressed proteins; the results revealed the differences in leaf tissue protein levels between modern and wild wheat genotypes in response to drought [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rick Tomato Genetics Resource Center, University of California, Davis. Germinated seeds were grown to the two-leaf stage in seedling cubes (Smithers-Oasis, Kent, OH) and then transferred into net pots (3.81 cm wide) filled with hydroteon clay balls (Hydrofarm, Seattle, WA) and continued to grow in half-strength Hoagland's nutrient solution (Hoagland and Arnon, 1950) to the four-leaf stage (Zhou et al, 2011). The greenhouse conditions were set at 25°C from 0500 to 2000 HR and 21°C during the remaining dark period with no supplemental lighting.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were ground into a fine powder under liquid nitrogen and then re-suspended in acetone supplemented with 10% trichloroacetic acid and 1% dithiothreitol (Sigma, St. Louis, MO). After incubation at -20°C overnight followed by centrifugation at 12,000 g n for 10 min at 4°C, protein pellets were collected and washed four times with pre-chilled acetone and finally evaporated to nearcomplete dryness (Zhou et al, 2009(Zhou et al, , 2011. After adding a dissolution buffer (1:10, w/v) consisting of 50 mM triethylammonium bicarbonate (TEAB) and 500 mM urea (Sigma), protein powder was incubated on ice for 10 min followed by centrifugation at 10,000 g n for 10 min.…”
Section: Methodsmentioning
confidence: 99%